2021
DOI: 10.3389/fgene.2021.690990
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Potential Candidate Genes of Colorectal Cancer in Response to Fusobacterium nucleatum Infection

Abstract: Objective: Recent investigations revealed the relationship between Fusobacterium nucleatum (Fn) infection and colorectal cancer (CRC). However, how the host genes changes contribute to CRC in response to Fn infection remains largely unknown.Materials and methods: In the present study, we aimed to comprehensively analyze microarray data obtained from a Caco-2 infection cell model using integrated bioinformatics analysis and further identify and validate potential candidate genes in Fn-infected Caco-2 cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Prior studies have revealed epigenomic and/or transcriptomic alterations induced by F. nucleatum in normoxia on non-cancerous cell lines including primary human colonic epithelial cells, human carotid artery endothelial cells 31 , human gingival fibroblasts 32 , 33 , rat osteoblasts 34 , and human immortalized oral epithelial cells 35 . Microarray data analysis of F. nucleatum infection of Caco-2 CRC cells, identified a role for CEP5 centrosomal protein that can impact cell cycle and apoptosis 36 . Other studies have focused on the RNA landscape of multiple F. nucleatum strains 37 or alterations in gene expression within F. nucleatum upon infection of Caco-2 cells 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have revealed epigenomic and/or transcriptomic alterations induced by F. nucleatum in normoxia on non-cancerous cell lines including primary human colonic epithelial cells, human carotid artery endothelial cells 31 , human gingival fibroblasts 32 , 33 , rat osteoblasts 34 , and human immortalized oral epithelial cells 35 . Microarray data analysis of F. nucleatum infection of Caco-2 CRC cells, identified a role for CEP5 centrosomal protein that can impact cell cycle and apoptosis 36 . Other studies have focused on the RNA landscape of multiple F. nucleatum strains 37 or alterations in gene expression within F. nucleatum upon infection of Caco-2 cells 38 .…”
Section: Introductionmentioning
confidence: 99%